Fivefold increase in derivation rates of mouse embryonic stem cells after supplementation of the media with multiple factors - J. Doungpunta (2018)
The objective of this study was to determine the ability of multiple-factor supplementation to augment derivation of mouse embryonic stem (mES) cells. Three factors, leukemia inhibitory factor (LIF), Parke-Davis 98059 (PD98059), and 6-bromoindirubin-3′-oxime (BIO), were added as supplements (individually or in a combination of all three) at two consecutive stages of culture; that is, from the start of blastocyst culture to the outgrowth stage, and from putting disaggregated outgrowth into culture medium to generation of primary mES colonies, respectively. The main outcome measure was the percentage of derivable mES cell lines, based on the number of blastocysts initially cultured. Three experiments demonstrated the following: (1) For the addition of individual single factor, only LIF yielded mES cell lines (6.2%), whereas a combination of all three factors resulted in the greatest number of mES cell lines (31.3%). (2) The advantages of a combination of multiple factors (LIF + PD98059 + BIO) were manifested only when they were used during the first stage of the culture and not during the second stage (31.6% vs. 6.2%, respectively). (3) The quality of the inner cell mass (ICM) outgrowth obtained from first-stage culture was studied. After alkaline phosphatase and Oct-4 staining, which documented pluripotency of the embryonic stem cells, outgrowths cultured in multiple factors (LIF + PD98059 + BIO) stained much stronger and in higher proportions than did those obtained after supplementation only with LIF (80% vs. 30%, respectively). © 2009 Elsevier Inc. All rights reserved.